The quality of the external auditor performance under international standards on auditing and external environment variables (Entrepreneurship Journal for Finance and Business, 2021)
The study dealt with diagnosing the quality of the external auditor's performance in view of international auditing standards and external environment variables. The study was based on a main hypothesis that states “the process of raising the quality of the external auditor’s performance and ensuring the fairness and objectivity of professional opinion within the auditor’s report that reflects the essence of control practices requires professional, technical and strict adherence to international auditing standards with consider the integrate with the external environment variables surrounding the entity subject to auditing" . In order to achieve the objectives of the study and test the validity of the hypotheses related to it, the researcher adopted the descriptive (correlational) approach, which aims to know the size and type of relationship between the variables, that is, to what extent the study variables are related to each other, sub-hypotheses were derived, which confirm the existence of a moral correlation with statistically significant between the international auditing standards and quality of the external auditor's performance, the external environment variables and quality of the external auditor's performance. This requires adoption a number of tools, including formulating and designing the questionnaire form in an accurate manner and making use of some previous studies in the process of designing that questionnaire in order to cover all study variables in a way that represents the study community correctly.The study reached a set of conclusions and recommendations, the most important of which are , one of the most important determinants of the success of external audit practices and achieving quality in the auditing performance is that the task must assign to a professional and competent external auditor possessing a number of personal qualities , scientific and professional qualifications, including integrity, objectivity and transparency in expressing a professional opinion , as addressed by the international auditing standard that requires exercising professional care, availability of skill, competence and training in the external auditor, he must possess the ability to understand international auditing standards and the conditions for their application, possess impartiality in the process of gathering evidence, familiarity with the affairs of the entity subject to auditing and the nature of its relationship with other external bodies. He must also possess a tendency of professional skepticism, which indicates alertness to cases that may indicate the possibility of a misrepresentation due to an error or fraud and critical evaluation of evidence , In addition to these features, the external auditor requires accuracy in determining the entity to which the auditor’s report are directed and justice in formulating this report as it is considered a link between the auditor and the needs and requirements of many users, including senior management, investors and creditors, in order to contribute to strengthening corporate governance and facilitate the process of making decision.